EFFECT OF STRATEGIC ORIENTATION AND ORGANIZATIONAL CULTURE ON FIRMS PERFORMANCE. ROLE OF ORGANIZATIONAL COMMITMENTS - Chayanan Kerdpitak; Chanathat Boonrattanakittibhumi (My University, 2020)
The main objective of the current study is to examine the direct impact of the strategic orientation and organizational culture on the firm performance of banks operating in the Thailand.Additionally, the study has also examined the mediating role of organizational commitment in the relationship between strategic orientation and firm performance, and between organizational culture and firm performance.The suitability of the activities of an organization is determined through innovation and strong culture, which contributes to the performance an organization (OP).A questionnaire based on structured questions was developed with reference to the objectives of the research.The data was analyzed using structural equation modelling that is regarded as technique of second generation.This is referred as second-generation technique due to some limitations of first-generation techniques.The response rate of the study is 63.4 percent.It was revealed by the results that significant and positive relation exists between hard/soft HR strategic orientations, continuance, and affective components of commitment.However, there was negative association of normative commitment with hard HR.The caring organizational attitude with its employees is regarded as soft HR and limited or rigid behavior is indicated by hard HR.The findings of the study have provided support to the proposed results.
Keywords: Organizational Leadership and Management Strategies